2018
DOI: 10.1007/jhep01(2018)018
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the supersymmetric mKdV hierarchy via Bäcklund transformations

Abstract: The integrability of the N = 1 supersymmetric modified Korteweg de-Vries (smKdV) hierarchy in the presence of defects is investigated through the construction of its super Bäcklund transformation. The construction of such transformation is performed by using essentially two methods: the Bäcklund-defect matrix approach and the superfield approach. Firstly, we employ the defect matrix associated to the hierarchy which turns out to be the same for the supersymmetric sinh-Gordon (sshG) model. The method is general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 79 publications
(151 reference statements)
0
14
0
Order By: Relevance
“…Moreover, based on this fact it has been shown that the spatial component of the Bäcklund transformation, and consequently the associated defect matrix, are also common and henceforth universal within the entire bosonic hierarchy [10,11]. This agrees More recently, in [1], this result has been extended to the supersymmetric mKdV hierarchy with the following defect matrix…”
Section: The Bäcklund Transformations For the Smkdv Hierarchymentioning
confidence: 63%
See 3 more Smart Citations
“…Moreover, based on this fact it has been shown that the spatial component of the Bäcklund transformation, and consequently the associated defect matrix, are also common and henceforth universal within the entire bosonic hierarchy [10,11]. This agrees More recently, in [1], this result has been extended to the supersymmetric mKdV hierarchy with the following defect matrix…”
Section: The Bäcklund Transformations For the Smkdv Hierarchymentioning
confidence: 63%
“…where m is the degree of the subspace G m according to Q, i.e., [Q, (1) and M(E) is its complement ( image). Now we can define the Lax pair as…”
Section: The Smkdv Hierarchymentioning
confidence: 99%
See 2 more Smart Citations
“…For theories defined on the whole line the quantum conservation laws have been studied in [17] where a suitable renormalization of the currents preserving conservation laws has been found. Classically it is possible to introduce boundary [58] and defects [59][60][61][62][63] but a systematic classification of possibly susy preserving boundaries and defects at quantum level is still lacking.…”
Section: Jhep06(2019)062mentioning
confidence: 99%